Architecture Design of An Intelligent Monitoring System for Turbine Filtration Device. Issue 1 (June 2021) - Yi, Jiangang; Bo, Wen
Abstract: In order to improve the operation efficiency of the turbine and reduce the failure rate of the equipment, this paper takes the inlet filter device of the turbine as the research object, comprehensively utilizes computer technology, machine learning, computer network and other technologies, and proposes a remote monitoring system of the turbine filter device based on industrial Internet cloud service and C/S architecture. The industrial process monitoring system is designed according to the actual situation of the industrial process. By connecting the system to the industrial Internet cloud service, the remote monitoring of the on-site running state and operation data of the equipment is realized. On this basis, the artificial neural network is proposed to realize the timely diagnosis and treatment of faults, and the operation and maintenance suggestions are put forward to improve the stability of equipment operation, reduce the maintenance cost of equipment, so as to improve the economic benefits of system operation and maintenance.